Born global family firms: a multiple case study. (28th October 2021) - Francioni, Barbara; Musso, Fabio; Masili, Giorgia
The principal aim of this study is to examine the factors that most influence the internationalisation process of born global family firms. To achieve this goal, we considered two main frameworks adopted in previous literature, which analysed specific factors and characteristics. Then, through a multiple case study, we verified if these factors and characteristics can enable or limit the internationalisation process of born global family firms. Our findings provided a significant confirmation for many of the factors considered, especially those related to the characteristics of top management. However, with reference to the analysis schemes adopted, not all the factors and characteristics considered resulted to be significant. Moreover, the proposed classifications did not prove to be completely suitable for interpreting the phenomena analysed. For this reason, a new framework, which summarises and reorganises the characteristics and factors to be analysed, has been developed.